2020
DOI: 10.3389/fphar.2019.01570
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine (MaZiRenWan) Improves Bowel Movement in Functional Constipation Through Down-Regulating Oleamide

Abstract: In a prospective, randomized, three-arms, controlled clinical study, Chinese Herbal Medicine MaZiRenWan (MZRW, also known as Hemp Seed Pill) demonstrates comparable efficacy with Senna for functional constipation (FC) during an 8-week treatment period. Both MZRW and Senna are better than a placebo; relative to Senna and a placebo, MZRW displayed a more sustained effect during the 8-week follow-up period. The characteristic pharmacological mechanism responsible for this observation is still unclear. To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our group has studied the pharmacology of MZRW and identified five representative active components, which can enhance colonic motility [ 21 ]. MZRW treatment in our previous study resulted in reduced levels of circulating oleamide, which is a known regulator of intestinal motility [ 22 ]. Further pharmacometabolomic analysis of MZRW for opioid-induced constipation can be explored when implementing a large-scale clinical trial in future.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has studied the pharmacology of MZRW and identified five representative active components, which can enhance colonic motility [ 21 ]. MZRW treatment in our previous study resulted in reduced levels of circulating oleamide, which is a known regulator of intestinal motility [ 22 ]. Further pharmacometabolomic analysis of MZRW for opioid-induced constipation can be explored when implementing a large-scale clinical trial in future.…”
Section: Discussionmentioning
confidence: 99%
“…Xuanhuang Runtong tablets (XHRTs) is a prescription composed of 9 Chinese herbal medicines, including Rehmannia glutinosa Libosch, Scrophulariae radix, Angelicae sinensis radix, Persicae semen, Cistanches herba, Cannabis fructus, Cassiae semen, and Aurantii fructus immaturus. The laxative effect of these Chinese herbal medicines has long been reported in the literature [ 11 14 ]. XHRT has a positive curative effect on functional constipation caused by yin deficiency, blood stasis, and senile functional constipation with reasonable safety and few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota is an important indicator of animal health. It was found that Chinese herb medicine mixture could up-regulate the abundance of beneficial flora in the broiler intestine ( Lactobacillus and Candida ), enhance intestinal immune mechanisms and accelerate intestinal motility [ 15 , 16 ]. In this experiment, CCHMA was added to the feed in a reasonable combination of seven herbs to improve the structure of the cecum flora, thereby improving the quality of animal products and ultimately achieving higher economic benefits.…”
Section: Introductionmentioning
confidence: 99%